Juvenile mild traumatic brain injury elicits distinct spatiotemporal astrocyte responses. Issue 3 (31st October 2019) - Clément, Tifenn; Lee, Jeong B.; Ichkova, Aleksandra; Rodriguez‐Grande, Beatriz; Fournier, Marie‐Line; Aussudre, Justine; Ogier, Michael; Haddad, Elizabeth; Canini, Frederic; Koehl, Muriel; Abrous, Djoher Nora; Obenaus, Andre; et al.
Abstract: Mild‐traumatic brain injury (mTBI) represents ~80% of all emergency room visits and increases the probability of developing long‐term cognitive disorders in children. To date, molecular and cellular mechanisms underlying post‐mTBI cognitive dysfunction are unknown. Astrogliosis has been shown to significantly alter astrocytes' properties following brain injury, potentially leading to significant brain dysfunction. However, such alterations have never been investigated in the context of juvenile mTBI (jmTBI). A closed‐head injury model was used to study jmTBI on postnatal‐day 17 mice. Astrogliosis was evaluated using glial fibrillary acidic protein (GFAP), vimentin, and nestin immunolabeling in somatosensory cortex (SSC), dentate gyrus (DG), amygdala (AMY), and infralimbic area (ILA) of prefrontal cortex in both hemispheres from 1 to 30 days postinjury (dpi). In vivo T2‐weighted‐imaging (T2WI) and diffusion tensor imaging (DTI) were performed at 7 and 30 dpi to examine tissue level structural alterations. Increased GFAP‐labeling was observed up to 30 dpi in the ipsilateral SSC, the initial site of the impact. However, vimentin and nestin expression was not perturbed by jmTBI. The morphology of GFAP positive cells was significantly altered in the SSC, DG, AMY, and ILA up to 7 dpi that some correlated with magnetic resonance imaging changes. T2WI and DTI values were significantly altered at 30 dpi within these brain regions most prominently in regions distant from the impact site. Our data show that jmTBI triggers changes in astrocytic phenotype with a distinct spatiotemporal pattern. We speculate that the presence and time course of astrogliosis may contribute to pathophysiological processes and long‐term structural alterations following jmTBI. Main points: A single juvenile mild traumatic brain injury induces 1) morphological astrocytic alterations that spread from the initial injury site to distal parts of the brain over time; 2) lasting region‐specific brain tissue abnormalities detectable on MRI.